Integrating Sharia and SRI Portfolio to Achieve Kaffah and Sustainability - Farah Amalia; Ratno Agriyanto; Harjum Muharam; Andi Sri Wahyuni (Journal of Islamic Monetary Economics and Finance, 2026)
This study explores integrating Sharia principles with Socially Responsible Investing (SRI) to achieve comprehensive Sharia values (kaffah) and sustainability for the case of Indonesia. Proposing screening criteria and forming a sustainable Sharia-SRI portfolio, the study compares its performance with Islamic-screened and conventional portfolios. Using shares from the Indonesian Sharia Stock Index (ISSI) and SRI-Kehati, and analyzing their daily closing prices for ten year period spanning from 2014 to 2023, the Wilcoxon Signed Rank Test reveals that the Sharia-SRI integrated portfolio yields higher returns than ISSI and SRI-Kehati over the long term. These findings suggest that integrating Sharia and SRI can address environmental and human rights issues, attract more investors, achieve kaffah and promote ethical investment practices.